"Let's Talk about It"-Explicit Discussions as a Way to Reduce the Resistance of Religious Jewish Science Teachers to Learning and Teaching about Evolution: A Case Study - Iris Alkaher; Marva Shmueli; Amos Dreyfus (MDPI AG, 2020)
Acknowledging the diverse perceptions about science-religion relationships among learners who come from various religious environments may increase learners' willingness to learn about evolution. This study is based on a zoology course designed for in-service teachers, which aimed to provide basic scientific knowledge about evolution using the Religious Cultural Competence in Evolution Education framework. The study explores whether learners who were resistant to evolution modify their attitudes and willingness to learn about it, and whether they develop respect toward learners who hold contradicting views. Using qualitative methods, the findings indicate that using the Religious Cultural Competence in Evolution Education framework increased some formerly "resistant" learners' willingness to learn about evolution and include it in their own teaching, albeit in varying degrees and with various reservations. The learners appreciated the freedom to express their challenges concerning evolution learning or teaching and became more willing to respect opposing perspectives, even though not all the religious learners accepted evolution as an explanation for the development of organisms. This study has international implications for bridging the gap between science and religion, thus reducing resistance to learning and teaching about evolution.